Ареал, еколого-ценотичні умови місцезростань та структура популяцій Bulbocodium versicolor (Ker.-Gawl.) Spreng. (Melanthiaceae) - Melnik, V.I.; Gritsenko, V.V.; Shevchenko, D.Ju. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2006)
The results of the study of geographical distribution, ecological and coenotical conditions of habitats, modern state of populations of Bulbocodium versicolor (Ker.-Gawl.) Spreng. (Melanthiaceae) are considered. Recommendations for created botanical reservations are elaborated.